Factores de riesgo para el neonato pequeño para la edad gestacional en un hospital de Lima - Tejeda Mariaca, J. Eduardo (2015)
Objectives. Identify risk factors for at-term small for gestational age newborns. Materials and methods. Retrospective cohort study using data from the Maternal Perinatal Information System of the Maria Auxiliadora Hospital of Lima, from the period 2000-2010. Maternal age, parity, education level, marital status, pregestational body mass index, number of prenatal care visits, presence of conditions such as preeclampsia, eclampsia, urinary tract infection and gestational diabetes as risk factors in small for gestational age newborns were evaluated. The weight for gestational age was calculated based on Peruvian percentiles. Crude relative risk (RR) and adjusted (ARR) were calculated with confidence intervals of 95% using log-binomial generalized linear models. Results. 64,670 pregnant women were included. The incidence for small for gestational age was 7.2%. Preeclampsia (ARR 2.0, 95% CI: 1.86 to 2.15), eclampsia (ARR 3.22, 95% CI: 2.38 to 4.35), low maternal weight (ARR 1.38; 95% CI: 1.23 to 1.54), nulliparity (ARR 1.32, 95% CI: 1.23 to 1.42), age ≥35 years (ARR 1.16, 95% CI: 1.04 -1.29), having prenatal care visits from 0 to 2 (ARR 1.43, 95% CI: 1.32 to 1.55) and 3 to 5 (ARR 1.22, 95% CI: 1.14 to 1.32) were risk factors for small for gestational age. Conclusions. It is necessary to identify pregnant women with risk factors such as those found to decrease the condition of small for gestational age. Actions should emphasize modifiable factors, such as the frequency of prenatal care visits.